Ultrastructure of last larval instar fat body cells of Pachycondyla (= Neoponera) villosa (Formicidae: Ponerinae): cytochemical and chemical analysis - José Zara, Fernando (2003)
The ultrastructure of the fat body cells (trophocytes) of the last larval instar of Pachycondyla (D Neoponera) villosa is presented. The cytoplasm is restricted to the cell periphery and to the smaller strips among the vacuoles, protein granules, lipid droplets, and around the nucleus. Cytochemically, the presence of basic amino acids in the protein granules and in the nuclei was observed by using the ethanolic phosphotungstic acid technique (EPTA). The lipid droplets stained for unsaturated lipids. This result was further confi rmed by gas chromatography and mass spectrometry, where the unsaturated fatty acids were identifi ed as oleic and linoleic acids together with saturated fatty acids such as palmitic and stearic acid. Carbohydrates (glycogen) were also detected in the fat body. The glycogen is present as ¯ particles distributed among the lipid droplets and sometimes attached to them.